دور السياسات الاقتصادية في مواجهة اختلال ميزان المدفوعات في الجزائر للمدة 1990-2018 - خالد حمادي حمدون المشهداني; حمدية عادل جليل (PROSPECTIVE RESEARCHES, 2023)
This research aimed to highlight the role of economic policies in facing the imbalance of payments in Algeria, by adopting the (Eviews 10) program. The stability test was used by applying the expanded Dicke-Fuller test, then conducting a normal distribution test. The research found that (95%) of the changes that occur in the balance of payments are explained by the independent variables included in the model and the rest is due to variables that were not included in the model. The research showed an inverse relationship between (exchange rate, interest rate, revenues, and imports) with the balance of payments, and a direct relationship between each of (display Money, expenditures, external debt, exports) with the balance of payments. The research reached a number of proposals, the most important of which is giving a prominent role to the exchange rate policy by adopting this variable as a tool to control foreign trade and enhance confidence in the local currency, which will have an impact on creating demand and raising growth rates. In GDP, which is reflected in reducing the imbalance in the balance of payments in Algeria?